Platelets, Thrombo-Inflammation, and Cancer: Collaborating With the Enemy - Palacios-Acedo, Ana Luisa; Mège, Diane; Crescence, Lydie; Dignat-George, Françoise; Dubois, Christophe; Panicot-Dubois, Laurence (Frontiers in Immunology, 2019)
Platelets are small anucleate cells present in the blood stream, their typical role in primary hemostasis has been well described. However, new evidence suggests that they have critically important roles in cancer progression and inflammation. Cancer cells can activate platelets, thus using them as physical shields from blood shear forces and natural killer (NK) cells. The activated platelets may also regulate hematopoietic and immune cell migration towards the tumor site; therefore, contributing to the cancer associated inflammation. The activation of platelets by cancer cells may also contribute to metastasis and cancer progression by stimulating deep venous thrombosis and neutrophil extracellular trap formations (NETs) that “hide” cancer cells. We strived to review the current literature to dissect the role of platelets in cancer associated thrombosis and tumor microenvironment inflammation.